hsdS, Belonging to the Type I Restriction-Modification System, Contributes to the Streptococcus suis Serotype 2 Survival Ability in Phagocytes - Xu, Bin; Zhang, Ping; Li, Weiyi; Liu, Rui; Tang, Jinsheng; Fan, Hongjie (Frontiers in Microbiology, 2017)
Streptococcus suis serotype 2 (SS2) is an important zoonotic agent in swine and humans. Anti-phagocytosis and survival in phagocytic cells and whole blood is essential for bacteria to be pathogenic. In this study, the host specificity determinant specificity subunit (coded by hsdS) of the Type I Restriction-Modification system and two peptidoglycan-binding proteins (coded by lysM and lysM’, respectively), which were simultaneously found to be subjected to transcript-level influence by hsdS, were identified to facilitate the anti-phagocytosis of SS2 to a microglia cell line BV2. Furthermore, they significantly enhanced its survival in BV2, whole blood, and a peroxidation environment (H2O2) (p < 0.05), yet not in the acidic condition based on statistical analysis of the characteristic differences between gene mutants and wild-type SS2. In contrast, another specificity subunit, coded by hsdS’, that belonged to the same Type I Restriction-Modification system, only significantly reduced the survival ability of SS2 in the acidic condition when in the form of a gene-deleted mutant (p < 0.05), but it did not significantly influence the survival ability in other conditions mentioned above or have enhanced anti-phagocytosis action when compared with wild-type SS2. In addition, the mutation of hsdS significantly enhanced the secretion of nitric oxide and TNF-α by BV2 with SS2 incubation (p < 0.05). The SS2 was tested, and it failed to stimulate BV2 to produce IFN-γ. These results demonstrated that hsdS contributed to bacterial anti-phagocytosis and survival in adverse host environments through positively impacting the transcription of two peptidoglycan-binding protein genes, enhancing resistance to reactive oxygen species, and reducing the secretion of TNF-α and nitric oxide by phagocytes. These findings revealed new mechanisms of SS2 pathogenesis.